Teach me-- everyday Italian. Volume 2, Celebrating the seasons [compact disc] - Mahoney, Judy (Teach me--., 2009)
Follow Marie and Peter as they plant a garden, visit the museums, picnic at the beach, celebrate the holidays and other events of the season. A perfect place to start exploring new languages for children of all ages as it introduces common words, phrases and concepts to the beginning language learner through delightful songs and story.